Genetic programs of neuronal degeneration in dendrite arborisation neurons. - Lee, Hui Min. (2010)
The neural system is a complex system that intertwines, connect and coordinate complex living organisms. Neurodegenerative diseases are due to the degeneration of nerve cells some of which undergo some form of dendrite pruning. In this project, we make use of a naturally occurring dendrite pruning process in the class IV dorsal dendritic arborisation (ddaC) neurons of the Drosophila melanogaster’s Peripheral Nervous System (PNS) as a model for neurodegeneration. With the application of reverse genetics through a genome-wide in vivo RNA interference (RNAi) screen using the Gal4-upstream activating sequence (UAS) system, we attempted to identify genes that involved in dendrite pruning in the Drosophila. A screen of 310 RNAi lines revealed 9 genes showed dendrite pruning defects at 16 hrs After Puparium Formation (APF). We focused our attention on the genes Katanin-60, Kat-60L1, Kap3 and CG33967. Quantification studies revealed that Kap3 had the highest percentage of dendrite pruning defect while CG33967 had the highest number of primary and secondary dendrites attached to the soma at 16 hr APF. The identification of genes involved in dendrite pruning aided our understanding of the molecular mechanism of neurodegeneration as well as proving that RNAi can be an efficient way to identify novel genes involved in dendrite pruning.